2009
DOI: 10.1007/s11671-009-9342-6
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Reaction and Subsequent Annealing to Synthesis Hollow Spherical Magnetite and Maghemite Nanocages

Abstract: Water-soluble hollow spherical magnetite (Fe3O4) nanocages (ca.100 nm) with high saturation magnetization are prepared in a one-pot reaction by sol-gel method and subsequent annealing to synthesise the maghemite (γ-Fe2O3) nanocages with similar nanostructures. The nanocages have been investigated by powder X-ray diffraction (XRD), transmission electron microscope (TEM), high-resolution transmission electron microscope (HRTEM), and superconducting quantum interference device (SQUID). The results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…In addition, Fe 3 O 4 also has desirable catalytic properties that can be used as electro-catalyst for oxygen reduction [4,5]. However, it has been proven to be challenging to produce stable Fe 3 O 4 nanoparticles with accurate control over size, and geometry [6]. The Fe 3 O 4 crystals tend to agglomerate into large clusters due to their high surface energy and spontaneous magnetization, which results in a loss of dispersity and effective surface area and therefore diminished catalytic activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fe 3 O 4 also has desirable catalytic properties that can be used as electro-catalyst for oxygen reduction [4,5]. However, it has been proven to be challenging to produce stable Fe 3 O 4 nanoparticles with accurate control over size, and geometry [6]. The Fe 3 O 4 crystals tend to agglomerate into large clusters due to their high surface energy and spontaneous magnetization, which results in a loss of dispersity and effective surface area and therefore diminished catalytic activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Complex magnetic properties of nanosized iron oxides have been widely discussed and a wide range of magnetic properties has been obtained [1,[56][57][58][59][60][61][62]. Dutta et al reported nearly defect-free maghemite nanocrystals of a size of about 7 nm, high saturation magnetization M S = 80 emu/g close to bulk value, whereas at the same time, very low coercivity H C = 20 Oe was obtained [63].…”
Section: Introductionmentioning
confidence: 99%
“…In the insert of Figure 6(a), the photographs demonstrate that the as-obtained samples can be magnetic separated by an external magnetic field. 26 This figure also illustrates the facile, fast separation process of the bi-component NPs during the experiments. The magnetization curves were measured as a function of temperature with different applied fields between 10 and 300 K using field-cooling (FC) and zero-field-cooling (ZFC) procedures.…”
mentioning
confidence: 84%